Heat transfer enhancement of a translating plate impinged by dual-slot nozzles with integrated multiple jets: a comparative study of single- and double-row configurations - Wu, Licheng; Kang, Can; Verdin, Patrick G.; Yin, Jin (Elsevier, 2026)
The thermal-fluid-structural behavior of a translating aluminum plate in an air-cushion furnace equipped with dual-slot nozzles integrated with multiple jets is numerically investigated, focusing on the effect of the jet-row number. Three configurations are considered: dual-slot without multiple jets (DS-NoMJ), with a single-row of multiple jets (DS-SRMJ), and with double rows of multiple jets (DS-DRMJ). The results show that increasing the jet-row number enhances convective heat transfer but significantly modifies the pressure distribution and deformation characteristics. The average Nusselt number increases by about 18% and 27% for DS-SRMJ and DS-DRMJ, respectively, compared with DS-NoMJ. However, temperature uniformity decreases as the number of jet rows increases, with the temperature uniformity index decreasing from 0.757 (DS-NoMJ) to 0.703 (DS-DRMJ). With DS-NoMJ and DS-SRMJ, the plate exhibits a stable wave-like deformation pattern with small amplitudes (7.39 mm and 8.59 mm), associated with symmetric recirculation and gradual pressure redistribution. In contrast, DS-DRMJ produces disordered vortical structures and localized stagnation pressure concentration, leading to high pressure difference between the upper and lower air cushions and severe central bulging of the plate, with maximum deformation reaching 23.74 mm. The single-row multiple-jet configuration provides the best compromise between heat transfer enhancement and aerodynamic stability, achieving intensified heat transfer while maintaining acceptable temperature uniformity and small deformation. These results clarify the role of the number of jet rows in coupling flow organization, pressure loading, and structural response.
Keywords: Air-cushion furnace; Multiple impinging jets; Number of jet rows; Temperature uniformity; Fluid-structure interaction; Plate deformation; 40 Engineering; 4012 Fluid mechanics and thermal engineering; 4017 Mechanical engineering